Fragrância da origem: um estudo sobre produtos masstige, imagem de país, etnocentrismo e xenocentrismo - Coelho, Miguel Al Behy Kanaan (2026)
Perfumery is a market where Traditional Luxury brands extend their lines to position themselves in the Masstige (Mass+ Prestige) products market, reaching a new market. This 11 way, the luxury brand reputation brings prestige to products that are more accessible for the general population, but with a high added value. The general objective of this study is to investigate the impact of the brand’s country-of-origin image on perceived brand prestige and consumers’ willingness to pay more among perfume brands in the context of an emerging market; and the following specific objectives: 1. To analyze the mediating role of brand prestige perception in the relationship between Brand Country-of-Origin Image and consumers’ Willingness to Pay More among perfume brands. 2. To analyze the moderating effects of the cultural dispositions of ethnocentrism and xenocentrism on the relationship between Brand Country-of-Origin Image and consumers’ perceptions of prestige and willingness to pay more for products that are more accessible to the general population but have high added value. A quantitative approach using Structural Equation Modeling (SEM) was adopted to analyze data obtained through a survey and Necessary and Sufficient Condition Analysis to understand the relationships between the constructs. The results indicate that Country Image positively impacts both Brand Prestige Perception and Willingness to Pay a Premium Price, in addition to being a necessary condition for the occurrence of these constructs. Brand Prestige mediates the relationship between Country Image and Willingness to Pay a Premium Price, and Xenocentrism emerged as a moderating construct in the relationships between Country Image, Brand Prestige, and Willingness to Pay a Premium Price in the context of international branding.